Habitat Preference of Surili Gunung Ciremai National Park - Kusumanegara, Agus; Kartono, Agus Priyono; Prasetyo, Lilik Budi (Department of Forest Resources Conservation and Ecotourism - IPB University, 2017)
Conversion of natural forest into plantation forest at Gunung Ciremai which managed by Perum Perhutani for three decades, gaves significant destructive impacts to sulrili’s habitat and triggering surili to disperse to the more secure habitat. After the change of forest function to conservation forest in 2004, preference habitat surili is unknowing. Therefore, the initial step of the conservation efforts to restore population were by analyzing the habitat preferences surili. Chi-square analysis and Neu analysis was used to analyze the habitat preferences surili. Research carried out from September to November 2016 in Gunung Ciremai National Park. Preferential habitats characteristic of surili on Gunung Ciremai National Park are such as elevation from 1.500 to 2.400 m above sea level, densely forest stand >50%, distance to the edge of the forest (0-665meter), distance to the settlement (0-806 meters), distance to the hiking trail (0- 1572 meters), surface temperature 16,3-18,5°C, steep slope (25-40%), preference for habitats that is secondary forest cover. Keywords: Gunung Ciremai National Park, preferential habitat, surili